Performance of solar dish stirling engine for remote area needs - Imansyah Ibnu Hakim; Hafizh Bramantya Rizaldi Putra (Badan Kerja Sama Teknik Mesin Indonesia, 2023)
The need for electricity is the main need of the Indonesian people, and everyone. In 2020, there are 433 villages without electricity in Indonesia. Indonesia has great potential as a source of renewable energy. According to the Ministry of Energy and Mineral Resources, Indonesia's total renewable energy potential is 417.8 gigawatts (GW). The greatest potential comes from the sun at 207.8 GW. One way to utilize the potential of solar energy is to use the Solar Dish Stirling Engine. This research uses an alpha stirling engine and uses air as the working fluid. This initial research of the solar dish Stirling engine aims to determine engine performance with parameters such as engine rotation speed, Stirling engine output power, and Stirling engine output power efficiency. The experiment was carried out using four variations of the piston arm length, namely 5 cm – 5 cm (LH-LC), 5 cm – 4.3 cm (LH-LC), 4.3 cm – 5 cm (LH-LC) and 4.3 cm – 4.3 cm (LH-LC), and used a 500 Watt halogen lamp as a substitute for the solar heat source. From the results of the study, the maximum rpm speed was obtained at 852 rpm with an arm length of 5 cm – 5 cm (LH-LC). The results of the study also showed that optimum engine rotation speed was found in the length of the arm 5 cm – 5 cm (LH-LC) with a value of 0.39 W at 839 rpm. Finally, it is known that the largest stirling engine efficiency is 6.5% at arm length 5 cm – 5 cm (LH-LC).